2019
DOI: 10.1371/journal.pone.0217306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the endobronchial stent microbial biofilm reveals bacterial communities that associate with stent material and frequent fungal constituents

Abstract: Endobronchial stents are increasingly used to treat airway complications in multiple conditions including lung transplantation but little is known about the biofilms that form on these devices. We applied deep sequencing to profile luminal biofilms of 46 endobronchial stents removed from 20 subjects primarily with lung transplantation-associated airway compromise. Microbial communities were analyzed by bacterial 16S rRNA and fungal ITS marker gene sequencing. Corynebacterium was the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Aside from fungal taxa, the existence of several bacterial taxa such as Corynebacterium (most common), Staphylococcus , Pseudomonas , Streptococcus , and Prevotella was also noted by the authors. Furthermore, some evidence indicating fungal–bacterial covariation was also observed in this study ( 230 ).…”
Section: Lung Transplantationsupporting
confidence: 85%
See 1 more Smart Citation
“…Aside from fungal taxa, the existence of several bacterial taxa such as Corynebacterium (most common), Staphylococcus , Pseudomonas , Streptococcus , and Prevotella was also noted by the authors. Furthermore, some evidence indicating fungal–bacterial covariation was also observed in this study ( 230 ).…”
Section: Lung Transplantationsupporting
confidence: 85%
“…They natively colonize the human oral cavity, nasopharynx, and GI tract (227)(228)(229). In a recent study, a group applied deepsequencing to analyze the microbial biofilms present on endobronchial stents (a silicone/steel tube that keeps the bronchial tubes open in patients affected by bronchial stenosis) in a patient cohort predominantly consisting of lung transplant recipients (230). The authors reported Candida spp.…”
Section: Lung Transplantationmentioning
confidence: 99%
“…It is likely that sphincterotomy performed for stent placement allowed bacteria to invade the main pancreatic duct . This story mirrors that in previous studies of biofilm covering pancreatic duct stents . Taken together, such a large difference in the final product contamination rate between autologous and allogeneic cases might result from the number of bacteria and their localization and colonization.…”
Section: Discussionsupporting
confidence: 65%
“…were found as well as Gm+ S. aureus and Gm− P. aeruginosa. 12 In addition to biofilms, silicone airway stents are subject to the adhesion of mucus and airway plugging. The use of 3D printing technology to make patient-specific silicone stents results in fewer AEs due to migration and reduced need for stent changes, but infections and mucus adherence are not addressed by shape.…”
Section: ■ Introductionmentioning
confidence: 99%
“…aureus and Gm– P. aeruginosa . In addition to biofilms, silicone airway stents are subject to the adhesion of mucus and airway plugging.…”
Section: Introductionmentioning
confidence: 99%